Transporter modulation of molnupiravir and its metabolite β-D-N4-hydroxycytidine across the blood-brain barrier in a rat - Chun-Hao Chang; Wen-Ya Peng; Wan-Hsin Lee; Ling Yang; Tung-Yi Lin; Muh-Hwa Yang; Tung-Hu Tsai (Communications Medicine, 2023)
Abstract Background The antiviral drug molnupiravir is an orally bioavailable prodrug of the nucleoside analog β-D-N4-hydroxycytidine (NHC), which is used to treat coronavirus disease 2019 (COVID-19). However, there is very little information on the barrier distribution of molnupiravir. Our hypothesis is that molnupiravir and NHC can penetrate the blood‒brain barrier (BBB) into brain tissue and that nucleoside transporters (equilibrative nucleoside transporters; ENT and concentrative nucleoside transporters; CNT) can modulate this process. Methods To investigate the mechanism of molnupiravir transport through the BBB, multiple microdialyses coupled to a validated ultra-high-performance liquid chromatography tandem mass spectrometry (UHPLC‒MS/MS) was developed to monitor dialysates, and nitrobenzylthioinosine (NBMPR; an inhibitor of ENT) was administered concomitantly with molnupiravir (100 mg/kg, i.v.) in the male rat. Results Here, we show that molnupiravir is rapidly metabolized to NHC in the blood and crossed the BBB in 20 min. Furthermore, when NBMPR is concomitantly administered to inhibit efflux, the concentrations of molnupiravir and NHC in the brain increased significantly. Conclusions In summary, molnupiravir rapidly transforms into NHC and crosses the BBB and reaches the brain at approximately 0.3-0.8% of the blood‒brain ratio. The maximum concentration of NHC in the blood and brain is above the average half maximal inhibitory concentration (IC50) of the drug required to treat severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, suggesting a therapeutic effect. The penetration of NHC is modulated by NBMPR. These findings provide constructive information on brain disorders in clinical patients with COVID-19.